The Impact of Prior Work-Experience on Student Learning Outcomes in Simulated Internships - Bayerlein, Leopold (Journal of University Teaching and Learning Practice, 2020)
In this paper, the extent to which a compulsory non-placement work-integrated learning (WIL) activity, in the form of a simulated internship, in an Australian undergraduate accounting program, created learning outcomes for students with different levels of prior work-experience is assessed. The paper extends prior, theoretically based literature by providing an exploratory evaluation of the experiences of students undertaking a specific simulated internship. This evaluation is important because it enables students and higher education providers to evaluate the extent to which a simulation is likely to meet the learning needs and expectations of individual students and student groups. Despite the critical importance of such an evaluation, prior literature has thus far focused on theoretically based evaluations and comparisons of simulated internships, with empirical evidence being largely absent from the literature. Using a series of semi-structured interviews with students, the current paper shows that the evaluated simulation was generally able to develop cognitive, skill-based, and affective learning outcomes, and that students’ learning outcomes were strongly influenced by their prior real-world work-experience. In addition, the paper also shows that the lived experiences of students within the simulation were much more multifaceted and diverse than anticipated in the prior literature. The findings of this paper are relevant for higher education providers and students planning to undertake a simulated internship, or other non-placement WIL activity. Potential challenges and opportunities for different groups of students arising in the analysed simulation are identified and discussed.